’Eating the planet’ Seeking a philosophy of food in the anthropocene - Bruckmeier, Karl (Socio.hu Társadalomtudományi Szemle, 2015)
This paper discusses possibilities of renewing the philosophical discourse on food as part of interdisciplinary approaches to understand the global changes of food systems and the transcultural consequences of these changes. Social and environmental changes in the epoch of the Anthropocene, of globalization, industrial food production, and genetic modification of food products, require interdisciplinary analyses. The philosophy of food did not become influential in the history of philosophy and not in present social and ecological food discourses, except in fragmentary themes as the ethics of food production and consumption. The traditions of interdisciplinary and synthetic thinking in philosophy give reasons to renew the philosophy of food to analyse and reflect the wider social, cultural and ecological problems of food production and consumption. Such critical analyses require, beyond empirical research and its assessment, knowledge syntheses, theoretical reflection and normative judgements. The themes include the paradoxes of modern food and agriculture systems: hunger and abundance of food, unequal distribution of resources and access to food in market systems, commodification and de–commodification of food and natural resources, the limited availability of natural resources for human consumption and the continuing economic “growth mania”. The metaphor “eating the planet” describes risks for food production and consumption under conditions of global social and environmental change. Why such a cognitive programme should develop under the name of philosophy is discussed with arguments referring to knowledge synthesis, critical analysis and the practical significance of the philosophy of food for searching solutions to food and resource problems. Keywords: philosophy of food; sustainable food production; globalization of food; changing cultures of food; food justice